Regional emperor penguin population declines exceed modelled projections - P. T. Fretwell; C. Bamford; A. Skachkova; P. N. Trathan; J. Forcada (Communications Earth & Environment)
Abstract Emperor penguin populations are predicted to decline rapidly over the current century owing to habitat loss in Antarctica arising from warming oceans and loss of seasonal sea ice. Previous work using very high-resolution satellite imagery from 2009 to 2018 revealed a population decrease of 9.5%, characterized by a continuous decline until 2016, with a slight recovery until 2018. Our study, for the sector 0° to 90°W, includes the recent period of sea-ice loss between 2020 and 2023 and provides a regional population update for around a third of the global population. We used supervised classification of very high-resolution imagery, linked to a Markov model and Bayesian statistics. Results indicate a significant reduction in emperor penguin numbers, variance in the methodology is relatively high, but provides a best fit estimate of 22% decline over the period equating to a reduction of 1.6% per year. This decline exceeds the predictions of demographic models based on high-emission scenarios. It is unclear whether the sector analyzed here reflects conditions around the entire continent and our results highlight the need to extend the analysis to all sectors of Antarctica to determine whether these trends are reflected elsewhere.